Retinoic Acid Receptor β Expression in Oral Precancer Progression - Prof Shaleen Chandra; Prof. Shalini Gupta; Dr. Namita Chandra (Elsevier, 2023)
Aim or Purpose: The burden of Oral Squamous Cell Carcinoma (OSCC) is huge because of the permanent impairment, high mortality and associated high cost of treatment. OSCC is often preceded by oral pre-cancer lesions/conditions (PMDs). Retinoic Acid (RA) has been identified as a regulator of cell proliferation, differentiation and apoptosis and thus is critical for tissue morphogenesis and homeostasis. Retinoic Acid pathway involves numerous genes that control its functioning. Amongst them RAR β is the important one which deals with mechanism of RA effect on cell and body as a whole. Retinoic acid signalling has been reported as aberrant in many types of cancer. RARs are the mediators of RA-signalling, hence studying tissue specific receptor expression may be an effective means of detecting aberrant signalling and early diagnosis in oral carcinogenesis. Materials and Methods: 20 oral precancer tissue samples (and 10 normal oral tissue samples were selected for the study. All tissue sample were immunostained with Retinoic Acid Receptor β primary and secondary antibody. Staining was graded by two independent pathologists and an average of their readings was taken. Results: Expression of Retinoic Acid Receptor β (RAR β) was highest in normal oral tissues and which decreased from mild to severe histopathological grades in oralprecancer cases. Decrease in expression of RAR β correlated with histopathological progression of oral precancer. Conclusions: Loss of RAR β expression in oral precancer progression can provide an opportunity for novel treatment strategies to be investigated using retinoids together with epigenetic modifiers that promote re-expression of silenced genes specially at the precursor level.